Epidemiological Investigation of Bloodstream Infections by Extended Spectrum Cephalosporin-Resistant Escherichia coli in a Taiwanese Teaching Hospital - Yan, Jing-Jou (American Society for Microbiology, 2004)
In an epidemiologic and case-control study including 30 case patients over a 3.5-year period in a Taiwanese university hospital, only β-lactamase inhibitor use and extended-spectrum cephalosporin use were identified as independent risk factors for nosocomial CMY-2-producing Escherichia coli bloodstream infection, and CMY-2 producers were found more prevalent than extended-spectrum β-lactamase-producing isolates.